2003
DOI: 10.1104/pp.103.028019
|View full text |Cite
|
Sign up to set email alerts
|

SAGE Analysis of Transcriptome Responses in Arabidopsis Roots Exposed to 2,4,6-Trinitrotoluene

Abstract: Serial analysis of gene expression was used to profile transcript levels in Arabidopsis roots and assess their responses to 2,4,6-trinitrotoluene (TNT) exposure. SAGE libraries representing control and TNT-exposed seedling root transcripts were constructed, and each was sequenced to a depth of roughly 32,000 tags. More than 19,000 unique tags were identified overall. The second most highly induced tag (27-fold increase) represented a glutathione S-transferase. Cytochrome P450 enzymes, as well as an ABC transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
96
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 47 publications
(44 reference statements)
10
96
0
1
Order By: Relevance
“…Both GST-U24 and GST-U25 have similar rates of activity toward TNT, and, in combination with other endogenous GSTs, there is likely to be considerable overlapping activity toward TNT in vivo. Although not up-regulated in our microarray study (Gandia Herrero et al, 2008), GST-U19, which is closely related to GST-U24 and GST-U25, can also be up-regulated in response to TNT (Ekman et al, 2003), and it is likely that GST-U19 also has activity toward TNT. Root length studies of knockout GST-U24 mutant plants were reported to have a similar response to TNT to wild-type plants .…”
Section: Glutathione-tnt Productsmentioning
confidence: 94%
See 3 more Smart Citations
“…Both GST-U24 and GST-U25 have similar rates of activity toward TNT, and, in combination with other endogenous GSTs, there is likely to be considerable overlapping activity toward TNT in vivo. Although not up-regulated in our microarray study (Gandia Herrero et al, 2008), GST-U19, which is closely related to GST-U24 and GST-U25, can also be up-regulated in response to TNT (Ekman et al, 2003), and it is likely that GST-U19 also has activity toward TNT. Root length studies of knockout GST-U24 mutant plants were reported to have a similar response to TNT to wild-type plants .…”
Section: Glutathione-tnt Productsmentioning
confidence: 94%
“…While we saw a decrease in glutathione pools in plants grown in TNT-contaminated soil, studies using monochlorobimane, which binds glutathione to form a fluorescent compound, indicated that glutathione pools increase in the presence of TNT (Mezzari et al, 2005). Additionally, gene expression studies in Arabidopsis show that glutathione reductases, which are involved in sustaining glutathione pools, can be upregulated in response to TNT treatment (Ekman et al, 2003).…”
Section: Glutathione-tnt Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Previously, GSTs had been shown to be upregulated in response to TNT Keywords: Arabidopsis thaliana, environmental pollutant, Glutathione transferases, TNT, xenobiotic detoxification, 2, 4, 6-trinitrotoluene treatment, and their involvement in TNT detoxification hypothesized. [8][9][10][11][12] Our study 13 investigated GST-U24 and GST-U25, the 2 Arabidopsis GSTs most highly upregulated in response to TNT under our treatment conditions. We demonstrated that Arabidopsis plants overexpressing GST-U24 or GST-U25 removed more TNT from soil and were more resistant to TNT toxicity than wild type plants, due to the direct glutathionylation of TNT.…”
mentioning
confidence: 99%